The Risk Factors of Physical Activity Behavior in Junior High School Students During the Covid-19 Pandemic - Indriani; Hayyatan Tayyibah (Universitas Ahmad Dahlan, 2023)
Background: The COVID-19 pandemic has indirectly limited the student’s space and physical activities which increases insufficiency of physically active or sedentary behaviors. Meanwhile, low physical activity is a major risk factor for health problems. This study aimed to determine the physical activity behavior of students in junior high school. Method: This research used a cross-sectional survey; the sample was school children in 34 provinces in Indonesia and was collected through the Physical Activity Questioner Children (PAQ-C) and ASAFA scale. The questionnaire was distributed through Google Forms to 138 junior high school students aged 12-15 years as the age range. A sample size was taken by simple random sampling and 136 valid questionnaires were then analyzed for the relationship between variables by using Kendall's tau test. Results: The results showed that 31.6% of 136 students had insufficient physical activity or sedentary levels, and 14.7% had an active level dominated by female students (13.2%). Based on analysis data, it is found that there is a strong relationship between social support (p= 0.006, r=0.006, r=0.93; 95% CI), nutritional status (p=0.001 r=0.89; 95% CI), and age (p=0.014 r= 0.38; 95% CI) with physical activity. On the other hand, the gender (p=0.091, r=0.27; 95% CI) and school category (p=0.172 r=0.03; 95% CI) do not affect physical activity. Conclusion: The schools should provide students' physical activity guidance in collaboration with parents which can be trained at home to reduce the sedentary behavior among students during the Covid pandemic.